Rancang Bangun Virtual Reality Tour Untuk Menunjang Wisata Ziarah Berbasis Website - Julianto, Indri Tri; Nursalapiah, Sopa (Institut Teknologi Garut, 2025)
Garut is a region known for its many pilgrimage sites that are considered sacred and revered. One of the pilgrimage destinations in Garut is the Sacred Tomb of Godog (Makam Keramat Godog). This pilgrimage tourism emphasizes religious values and is visited with the purpose of seeking blessings and prayers from those believed to hold a special status in the eyes of God. Information about this pilgrimage site is still obtained from personal stories and digital platforms such as blogs. However, this information is only presented in the form of text and images. In addition, the information provided about the Sacred Tomb of Godog is still limited due to the lack of specific sources of information. With the development of technology, Virtual Reality can be utilized as a medium to introduce the Sacred Tomb of Godog and assist people who have limited accessibility to visit the pilgrimage site. This research aims to design and develop a Virtual Reality Tour for pilgrimage tourism that can help tourists or potential visitors who face distance limitations, have accessibility constraints, and increase tourist interest in visiting pilgrimage sites. The method used in this research is the Multimedia Development Life Cycle (MDLC), which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. The testing technique used in this research is alpha testing using the black box method. The result of this research is a website-based Virtual Reality Tour to support pilgrimage tourism, which features pilgrimage information, Google Maps, directional guide features (hotspots), audio, and a chatbot.